Pengembangan Sistem Pendukung Keputusan untuk Pengendalian Persediaan Bahan Baku ( Studi Kasus Pada PT. Ready Mix Concrete ) - Fauzan Azmi; Susy Susmartini; Yuniaristanto - (Performa: Media Ilmiah Teknik Industri, 2003)
PT. RMC, a company based on make to order which producing ready mixed concrete has not applied acertain ordering method yet. Giving letter of delivery and job-mix to logistics department close to production execution time make logistics department cannot determine requirement of material. Beside that, logistics department works based on work instrument and manual recording so that there are still found many problems which effect on pile up or shortage.It needs a method which can provide the decision about material ordering time and quantity so that result minimum total inventory cost. The method is developed as Decision Support System (DSS). It uses Material Requirement Planning concept (MRP) with daily phased. Determining economic ordering lot size uses static Economic Order Quantity (EOQ) with safety stock (SS). DSS determine Q order if inventory decrease until reach Reorder Point (ROP). With DSS, input and edit data become easier thanbefore.In validation, the proposed method is compared with the current method that result the total inventory cost of proposed method lower than current method. The cost reduction is 10,31 % or Rp. 23.351.790,97439 per month.